2015
DOI: 10.5897/ajmr2015.7462
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biodegradation studies of cow dung modified epoxy with epoxy using an indigenously developed bacterial consortium

Abstract: Thermoplastic-based polymers and their blends are recalcitrant in nature. Based on their extensive use, huge amount of polymeric waste is being produced annually, which impart serious threat on the natural ecosystem. Considering this scenario, it is needed to take some immediate actions to keep the ecosystem dynamic and secure. Therefore, this study was carried out in order to evaluate an indigenously developed bacterial consortium for the biodegradation of epoxy and a blend of epoxy with cow dung that is cow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…TGA is an analytical technique used to determine a material's thermal stability and its fraction of volatile components by monitoring its weight variation as a function of a constant heating rate in a controlled atmosphere. Several thermogravimetric studies on the biodegradation of polymers revealed that the decomposition temperatures of polymers shift to lower temperatures with longer temperature spans after degradation in comparison to polymers that have not been degraded [58,[64][65][66][67]. In some of these studies, TGA was combined with simultaneous differential thermal analysis (DTA) and derivative thermogravimetry (DTG) to gain a better understanding of the thermal properties of the biodegraded studied polymers [66,67] The average molecular weight of a polymeric material has a direct effect on its intrinsic viscosity; the higher the average molecular weight, the greater the intrinsic viscosity.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%
“…TGA is an analytical technique used to determine a material's thermal stability and its fraction of volatile components by monitoring its weight variation as a function of a constant heating rate in a controlled atmosphere. Several thermogravimetric studies on the biodegradation of polymers revealed that the decomposition temperatures of polymers shift to lower temperatures with longer temperature spans after degradation in comparison to polymers that have not been degraded [58,[64][65][66][67]. In some of these studies, TGA was combined with simultaneous differential thermal analysis (DTA) and derivative thermogravimetry (DTG) to gain a better understanding of the thermal properties of the biodegraded studied polymers [66,67] The average molecular weight of a polymeric material has a direct effect on its intrinsic viscosity; the higher the average molecular weight, the greater the intrinsic viscosity.…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%
“…Strain MK3 (DQ318884), Bacterium Te68R Strain PN12 (DQ423487), Pseudomonas putida Strain PW1 (EU741798), and Enterobacter sp. Strain Lna3 (DQ205431), were selected on the basis of their pre-identified potential to act upon LDPE (Soni et al 2009;Kapri et al 2010) and epoxy and its blends (Negi et al 2009;Raghuwanshi et al 2015), respectively. The cultures were revived by inoculating into 5.0 mL nutrient broth test tubes at optimum pH (7 ± 0.2) and temperature (35 ± 1°C).…”
Section: Bacterial Consortiummentioning
confidence: 99%
“…The calculated amount (CFU mL -1 ) of each mid-log phase bacterial strain was mixed to form bacterial consortium (Goel et al 2011). The compatibility test of each strain was conducted prior to the preparation of consortium as described earlier (Raghuwanshi et al 2015;Goel et al 2011).…”
Section: Bacterial Consortiummentioning
confidence: 99%
See 1 more Smart Citation
“…Medicinal plants play an important role in the livelihood worldwide and are used as raw materials for the extraction of active constituents in pure form (eg., alkaloids such as quinine and quinidine from cinchona bark, emetine from ipecacuanha root, glycosides from digitalis leaves, sennosides from senna leaves), as precursors for synthetic vitamins or steroids and as preparations for indigenous and herbal medicines [3]. Medicinal plants are the localized and global heritage of natural antioxidants in addition to other significant bioactive leads that are implemented in the prevention and treatment of diseases such as atherosclerosis, heart stroke, diabetes, cancer, and the ageing process that is prevalent in both rural and urban areas [4,5]. India's forests are the fundamental repository for a plethora of fragrant plants.…”
Section: Introductionmentioning
confidence: 99%